Ownership Structures and Earnings Management in Nigerian Oil Marketing Firms - O. Gbegi, Daniel; A. Abubarkar, Ibrahim; O. O. Josiah , Michael; Titus, Ibrahim (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The practice of altering financial statements by the management, mislead stakeholders and many questions and concerns are raised about credibility and quality of financial statement presented by the oil marketing firms in Nigeria. Based on the foregoing, this study assessed ownership structures and earnings management in Nigerian oil marketing firms. The study employed ex-post factor research design. Population of the study comprised of 10 oil marketing firms listed in the Nigerian stock exchange as at 31st December, 2017. The data for the study were collected from the annual report and accounts of the sampled companies for the period 2011-2017. Analysis was done using multiple regression analysis. The variables are ownership structures as independent variable represented by insider ownership, institutional ownership, block holding, and foreign ownership and discretionary accruals using the Modified Jones Model represent earnings management as dependent variable. Findings of this study showed that ownership structure have significant and positive effect on earnings management. The study therefore recommends that Oil marketing companies in Nigeria should encourage the principle of insider, institutional, block holding and foreign ownership this will in effect, boost their activities and will yield more returns to the oil companies thereby reducing the levels of earnings management.